Recent progress in caron-based stimulus-responsive electromagnetic interference shielding materials - Ying Li; Kaiyou Wu; Yudi Li; Siren Guo; Linlin Zhao; Yifan Guo; Wei Feng; Xulin Yang; Pan Wang; Kui Li; David Hui; Zuowan Zhou (Nanocomposites)
Intelligent electromagnetic interference (EMI) shielding materials with adaptively adjustable structure and performance under external stimuli hold great potential in developing new generation of intelligent EMI shielding materials. In this review, the latest and most impressive works of advanced materials for stimulus-responsive EMI shielding are highly focused on. Based on stimulating sources, the smart EMI materials are discussed in five categories: mechanical-, temperature-, electrical-, humidity-responsive and others. The key information, including structural design principle, EMI behavior, and structure-function relationship, is extracted and well organized with profundity and easy-to-understand approach. What’s more, the merit and demerit are revealed by comparison. Finally, a profound comment on the stimulus-responsive EMI materials as well as challenges are proposed, and the future directions are forecasted. Schematic illustration for stimulus-responsive EMI shielding, including mechanical-responsive (top left) (Reproduced with permission. Copyright 2021, Elsevier), temperature-responsive (top right) (Reproduced with permission. Copyright 2021, Elsevier; Reproduced with permission. Copyright 2022, The Authors, Elsevier), electrical-responsive (bottom right) (Reproduced with permission, Copyright 2015 Springer Nature), humidity-responsive (bottom) (Reproduced with permission. Copyright 2018, Elsevier), and others (bottom left) (Reproduced with permission. Copyright 2022, American Chemical Society; Reproduced with permission. Copyright 2020, Wiley-VCH).